Surface functionalized mesoporous polydopamine nanocomposites for killing tumor cells through collaborative chemo/photothermal/chemodynamic treatment - Yi Ouyang; Yan Chen; Ting Xu; Yihao Sun; Sheng Zhao; Chunmei Chen; Yixin Tan; Liang He; Hui Liu (Exploration of Drug Science)
Aim: The development of a collaborative strategy with improved efficacy holds great promise in tumor treatment. This study aims to develop an effective collaborative strategy based on functionalized mesoporous polydopamine (MPDA) nanocomposites for killing tumor cells. Methods: MPDA nanoparticles were synthesized and functionalized with camptothecin (CPT) payload and manganese dioxide (MnO2) coating to construct MPDA-CPT-MnO2 nanocomposites. Results: When uptaken by tumor cells, the nanocomposites can degrade to produce O2, release CPT, and generate manganese (Mn2+) under the stimulation of hydrogen peroxide (H2O2) and acid. The released CPT and Mn2+ can act as chemotherapeutic drug and Fenton-like agent, respectively. Abundant reactive oxygen species (ROS) are generated in 4T1 tumor cells through an Mn2+-mediated Fenton-like reaction. After that, the generated Mn4+ can react with glutathione (GSH) through redox reaction to produce Mn2+ and deplete GSH, disrupting the reducing capacity and benefiting the production of ROS in tumor cells. Under laser irradiation, the nanocomposites can generate hyperthermia to promote the production of ROS. Conclusions: The developed MPDA-CPT-MnO2 nanocomposites can kill tumor cells through collaborative chemo/photothermal/chemodynamic therapy (CDT).